Pelatihan Pembuatan VCO Dengan Metode Fermentasi Untuk Mendukung Kompetensi P5 Siswa - Kumaji, Syam S.; Uno, Wirnangsi D.; Aydalin, Regina Valentina; Febriyanti, Febriyanti; Yusuf, Daud; Kobi, Wiwin; Pratama, M.Iqbal Liayong (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
This activity aims to enhance students' competencies in the field of entrepreneurship through training in the production of Virgin Coconut Oil (VCO) using the fermentation method, as part of the implementation of the Pancasila Student Profile Strengthening Project (P5). The method employed involved educational sessions and hands-on training based on an experiential learning approach, involving 30 eleventh-grade students. The activity included theoretical introduction, practical VCO production, packaging, and marketing planning. Evaluation results indicated a significant increase in students' knowledge from 42% to 85%. Students demonstrated strong practical skills throughout the VCO production process, along with the development of entrepreneurial attitudes such as responsibility, collaboration, and creativity. This training proved effective as a contextual learning medium that reinforces Pancasila values and 21st-century skills.